2018
DOI: 10.1016/j.bja.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta-blockers on cancer recurrence and survival: a meta-analysis of epidemiological and perioperative studies

Abstract: Beta-blocker use had no evident effect on CR. The beneficial effect of beta-blockers on DFS and OS in the epidemiological or perioperative setting remains variable, tumour-specific, and of low-level evidence at present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 51 publications
2
64
0
3
Order By: Relevance
“…According to a recent meta-analysis by Yap A. et al, taking into consideration various tumor types including melanoma, there was no evidence that beta-blockers had any effect on recurrence or tumor specific survival [24]. Our results are also in accordance with previous registry-based studies by Livingston E. et al in the Netherlands [25] and a similar study by McCourt et al in the UK [26], that both failed to prove a survival benefit from the beta-blocker treatment among melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent meta-analysis by Yap A. et al, taking into consideration various tumor types including melanoma, there was no evidence that beta-blockers had any effect on recurrence or tumor specific survival [24]. Our results are also in accordance with previous registry-based studies by Livingston E. et al in the Netherlands [25] and a similar study by McCourt et al in the UK [26], that both failed to prove a survival benefit from the beta-blocker treatment among melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical evaluation of propranolol as a neoadjuvant or perioperative treatment for breast cancer is on-going [13][14][15][16]. However, a recent contradictory study has reported no benefit between prescribed beta-blockers and survival [17], whereas a different study using the basal-type MDA-MB-231 breast cancer cell line model showed that beta-adrenergic receptor (ADRβ2) agonism (rather than antagonism) inhibited tumour proliferation [18]. Further studies are required to explain these discordant findings, which could result from variance in (a) in vitro cell line models; (b) patient cohort selected in pre-clinical studies; (c) pharmacologic selectivity of prescribed beta-blockers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different cellular and molecular mechanisms by which the sympathetic nervous system can influence tumour progression have been identified, including DNA repair, oncogene activation, inflammation and immune response, haematopoiesis, angiogenesis, cell survival and apoptosis . Several observational epidemiologic studies have documented associations between exposure to β‐adrenergic antagonists and reduced progression of some cancers, though some inconsistencies exist, which suggests that randomised controlled studies are needed.…”
Section: The Key Role Of the Toementioning
confidence: 99%